Empowering TVET Graduates The Role of English Proficiency in Global Competitiveness - Amy Zulaikha, Mohd Ali (UMPSA, 2025)
Malaysia’s Technical and Vocational Education and Training (TVET) system plays a pivotal role in fortifying the nation’s economic competitiveness, particularly in addressing the complexities of the Fourth Industrial Revolution (IR 4.0).